1997
DOI: 10.1159/000289117
|View full text |Cite
|
Sign up to set email alerts
|

Prior Treatments in a Group of Tinnitus Sufferers Seeking Treatment

Abstract: Background: Tinnitus is a common problem for which many treatments have been proposed and implemented. Patients tend to seek renewed treatment after treatment failure. The aim of this descriptive study was to describe a group of consecutive tinnitus patients in terms of prior treatments received. Methods: Sixty-nine tinnitus patients seeking treatment were asked about prior treatments and completed the short Tinnitus Effect Questionnaire (TEQ). Four groups were obtained: No treatment (n = 24), acupuncture (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…There were also comments regarding complementary medicine, which is commonly used by tinnitus patients, at least in our experience (30). There were, however, mostly negative comments regarding these treatments.…”
Section: Treatment Experiencesmentioning
confidence: 77%
“…There were also comments regarding complementary medicine, which is commonly used by tinnitus patients, at least in our experience (30). There were, however, mostly negative comments regarding these treatments.…”
Section: Treatment Experiencesmentioning
confidence: 77%
“…A novel finding of the present study is that 16 per cent of patients seen for vestibular assessment had tried some form of complementary therapy to help with their symptoms. This finding is surprisingly low if one considers that a previous report showed that 65 per cent of tinnitus patients had tried complementary therapy before seeking clinical help 10 and that up to one-third of the US adult population had used complementary therapy in 2002. 3 There are two potential sources of bias in this study that may help to explain this finding.…”
Section: Discussionmentioning
confidence: 90%
“…The financial burden upon the patient who had tried six complementary therapy approaches must have been significant. Further, Andersson 10 has noted an association between repeated use of complementary therapy, and implied disappointment at failed therapy, and ability to change in tinnitus patients. A reasonable clinical concern might be raised over this possibility in vestibular patients.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Contrarily, previous treatment has shown worse outcomes in some previous studies. 45 However, it may be that some participants may have sought alternative therapies which have no evidence for tinnitus. For this reason, it would be useful to examine specific types of previous treatments in future studies to distinguish between those who had evidence-based interventions before enrolling to ICBT than those who did not.…”
Section: Discussionmentioning
confidence: 99%